2019
DOI: 10.1186/s41239-019-0150-5
|View full text |Cite|
|
Sign up to set email alerts
|

Case study of creativity in asynchronous online discussions

Abstract: It is vital for online educators to know whether the strategies they use help students gain twenty-first-century skills like creativity. Unfortunately, very little research exists on this topic. Thus, the purpose of this study was to determine whether participation in online courses can help students develop creativity using asynchronous online discussions, textbooks, and teacher developed materials. A case-study approach was used and one professor, recognized by her peers for her expertise in online education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 12 publications
0
18
0
1
Order By: Relevance
“…Indirect instruction, also known as asynchronous instruction, is a type of communication in which students communicate with the teacher and classmates at different times through e-learning platforms. Asynchronous discussion boards allow a large number of students to participate and interact with one another on a specific topic (Corfman & Beck, 2019). They provide students with indirect interaction with their course content in a variety of interesting and versatile ways (Lalima & Dangwal, 2017).…”
Section: Remote Online Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Indirect instruction, also known as asynchronous instruction, is a type of communication in which students communicate with the teacher and classmates at different times through e-learning platforms. Asynchronous discussion boards allow a large number of students to participate and interact with one another on a specific topic (Corfman & Beck, 2019). They provide students with indirect interaction with their course content in a variety of interesting and versatile ways (Lalima & Dangwal, 2017).…”
Section: Remote Online Learningmentioning
confidence: 99%
“…They provide students with indirect interaction with their course content in a variety of interesting and versatile ways (Lalima & Dangwal, 2017). Along with teacher-developed online materials, asynchronous discussion boards are frequently used as a central component of courses (Corfman & Beck, 2019).…”
Section: Remote Online Learningmentioning
confidence: 99%
“…Within online learning management systems such as Moodle, asynchronous discussion boards are a central component of many courses (Cho & Tobias, 2016; Pena-Shaff & Altman, 2015). Gao et al (2013) identified four ways that online instructors organize asynchronous online discussions, the most common of which was termed as a constrained environment wherein instructors provide students with frames of reference or sentence starters to orient students toward certain responses (Corfman & Beck, 2019). In identifying ways that teachers can cooperatively facilitate the communication of learner beliefs beyond self-reported survey responses, Zhong (2012) suggested structuring opportunities into the curriculum.…”
Section: Methodsmentioning
confidence: 99%
“…According to Abdous (2011) and Corfman and Beck (2019) feedback quality should cover constructive criticism, encouragement, fixing misconceptions and give further information. Berge (2008) stated automation allows advanced ways of providing feedback to learners.…”
Section: D) Feedback For Studentsmentioning
confidence: 99%